Testimony and Violence in the Novel Insensatez, by Horacio Castellanos - Murillo Ramírez, Guillermo (2022)
The article analyzes the testimony and violence in the novel Insensatez, by Horacio Castellanos—considering his role of intellectual in testimonial intervention—the figure of the torturer, the violated bodies and the dehumanization of the indigenous community. Thus a contrast is established between the testimonies of the report Guatemala: Nunca más and those appearing in the novel, to determine the development of themes such as rationality, madness and power through the application of Cultural Studies.